Story-Telling Dengan Boneka Tangan Dalam Upaya Pendidikan Kesehatan Etika Batuk Pada Anak Sekolah Dasar - Aprilia Nuryanti; Rahayu Setyaningsih (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
Upper respiratory tract infections (URTIs) are a major cause of morbidity and mortality among children worldwide. Poor hygiene behaviors, such as coughing without covering the mouth, contribute significantly to the transmission of these infections. Therefore, education on proper coughing etiquette is essential, particularly in school environments. Storytelling is an engaging and age-appropriate approach for delivering health education to children, as it effectively promotes hygiene awareness and self-protective behaviors. This community service activity was conducted using lectures, demonstrations, and storytelling with hand puppets among elementary school children aged 6–7 years at SD Negeri Mojosongo 1 No. 045, Jebres District, Surakarta City, on December 16, 2025. The activity lasted approximately 60 minutes and involved 22 students. Observational findings indicated that all participants were actively engaged throughout the session. All students were able to wear masks correctly and perform proper handwashing techniques. Additionally, most students demonstrated correct mask disposal (68%) and appropriate coughing etiquette (59%). Through this program, children were taught proper coughing techniques using hand puppet storytelling combined with direct demonstrations. The activity increased awareness of coughing etiquette and encouraged the adoption of healthy behaviors in daily life. This program is expected to contribute to reducing the transmission of respiratory infections, promoting healthier lifestyles among children, and supporting overall public health.